Creation and annihilation of topological meron pairs in in-plane magnetized films - N. Gao (Nature Portfolio, 2019)
A meron is one half of a skyrmion but whether a single meron pair can be created and stabilized remains a challenging question. Here, Gao et al. develop a method to create and stabilize individual pairs of merons in a continuous Py film by local vortex imprinting from Co disks.